2016
DOI: 10.1155/2016/9015802
|View full text |Cite
|
Sign up to set email alerts
|

In VitroAntimicrobial Activity of Spices and Medicinal Herbs against Selected Microbes Associated with Juices

Abstract: In the present investigation, comparison of antimicrobial activities of different spices, Curcuma longa, Zingiber officinale, and Mentha arvensis, and medicinal herbs, such as Withania somnifera, Rauvolfia serpentina, Emblica officinalis, Terminalia arjuna, and Centella asiatica, was evaluated. Different extraction solvents (acetone, methanol, ethanol, and water) were used and extracts were examined against Bacillus cereus, Serratia sp., Rhodotorula mucilaginosa, Aspergillus flavus, and Penicillium citrinum is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 47 publications
1
25
0
1
Order By: Relevance
“…[1,2,3,4,5] Most common materials used for controlling food spoilage are chemicals that have serious effects on human health. Consequently, great efforts have been spent for discovering safe effective natural materials which could be used in food preservation [6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…[1,2,3,4,5] Most common materials used for controlling food spoilage are chemicals that have serious effects on human health. Consequently, great efforts have been spent for discovering safe effective natural materials which could be used in food preservation [6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In a similar study Akgul & Kivanc (1989) reported the inhibitory effect of Cumin against S. aureus and K. pneumoniae and P. aeruginosa. Sunilson et al, (2009) andDhiman et al, (2016) reported the antimicrobial activities of Turmeric against different foodborne pathogens. Our study is in agreement with the results of their studies.…”
Section: Resultsmentioning
confidence: 99%
“…Spices, herbs, and their constituents are generally recognized as safe (GRAS) and approved by several regulatory agencies new technologies in food preservation lead to less use of preservatives and the use of antimicrobials from the natural sources [12]. In this context, spices appear to be promising natural products due to their antimicrobial effects and the compounds that exhibit this effect.…”
Section: Resultsmentioning
confidence: 99%